1969
DOI: 10.1111/j.2044-8295.1969.tb01219.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Imaging on Signal‐to‐noise Ratio, With Varying Signal Conditions

Abstract: Perky's finding, that an observer confuses his internal imagery with a normally supraliminal stimulus, has been reinterpreted in signal detection language. Two experiments compared a task where the subject was asked concurrently to image items and discriminate signals from noise to a task where the subject only discriminated signals. The subject's criterion was slightly higher in the imaging task and sensitivity (d′) was significantly lower, whether the imaging task was given before or after the discrimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…As expected, the results show a clear Perky effect, as imagined lines reduced acuity. The reduction is 17.6% when the imagined lines are “ON” the target, in line with Segal and Fusella (1970), Reeves (1980), and Craver-Lemley and Reeves (1987, 1992). The Perky effect was attenuated if the image was shifted off target, in the present research from 17.6 to 6.3% (i.e., baseline No Image – image OFF), also in line with Craver-Lemley and Reeves (1987).…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…As expected, the results show a clear Perky effect, as imagined lines reduced acuity. The reduction is 17.6% when the imagined lines are “ON” the target, in line with Segal and Fusella (1970), Reeves (1980), and Craver-Lemley and Reeves (1987, 1992). The Perky effect was attenuated if the image was shifted off target, in the present research from 17.6 to 6.3% (i.e., baseline No Image – image OFF), also in line with Craver-Lemley and Reeves (1987).…”
Section: Resultssupporting
confidence: 53%
“…In our earlier work, we argued in favor of analogous spatial behavior but against substitutability (Arterberry et al, 2002), based on empirical findings concerning the so-called Perky effect, in which visual images, analogous to real masking stimuli, can suppress perception of real visual targets (as discovered by Perky, 1910). The Perky effect is ubiquitous in studies of percept-image interactions, with the imagined stimulus depressing sensitivity to briefly flashed visual targets by 15% or better (0.8 d′ units or more; Segal and Fusella, 1970; Craver-Lemley and Reeves, 1987, 1992; Ishai and Sagi, 1997). In the Perky experiments, the experimenter requested that the subject project his or her visual image in the location of the visual target.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note, however, that Pearson et al (2008) also reported that when the background was 100% illuminated (i.e., a white background, as in the present study), their participants performed similarly under the conditions of viewing passively and generating a mental image. Besides, Segal and Fusella’s (1969, 1970) early studies demonstrate that a person’s sensitivity to detect a visual (or auditory) target was lowered when he/she imaged that stimulus in the same sensory modality. Such modality-specific suppression during mental image generation has recently been observed in primary sensory areas in humans (i.e., visual and auditory cortices, see Daselaar et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…First, there is evidence of competition between mental imagery and perceptual processing when they share the same sensory modality. Holding a visual image selectively interferes with the detection of a faint visual signal, and, likewise, auditory images interfere with the detection of auditory stimuli (Segal & Fusella, 1969). The reverse relationship also holds: judged vividness of visual images is reduced by simultaneous performance of a visuospatial task, and auditory image vividness is decreased by counting aloud (Baddeley & Andrade, 2000).…”
mentioning
confidence: 99%